Stock Returns Predictability and Market Timing Trading : Evidence from Malaysian Stock Market - Nguyen, Thi Tuyet Nhung (2011)
This study aims to re-examine the predictability of Malaysian stock returns and investigates whether the predictability can be exploited to earn abnormal returns using market timing strategy with consideration of transaction costs. Using quarterly and monthly data covering the period from January 1987 to December 2010, the regression results shows that KLCI excess returns are statistically related to change in lending interest rate, exchange rate, money supply and industrial production index. Recursive predictions derived from the optimal regression models are only capable of correctly predicting the positive signs of actual excess returns, whereas the forecasting accuracy of actual negative returns is very low, especially under quarterly trading basis. The results also indicate that the market timing strategy constructed on the basis of the recursive predictions only dominate the naïve buy-and-hold strategy in monthly trading frequencies. Particularly, under 0% and 0.8% transaction costs scenarios, the strategy provides higher returns and less riskiness as compared to the benchmark. However, under 1.4% transaction costs scenario, the market timing strategy does not deliver higher average returns than buy-and-hold strategy.